2013
DOI: 10.1371/journal.pone.0079436
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Its Prospective Association with Components of the GH-IGF-Axis, Insulin Resistance and Body Adiposity Measures in Young Adulthood – Insights from Linear and Quantile Regression Analysis

Abstract: BackgroundBreastfeeding may lower chronic disease risk by long-term effects on hormonal status and adiposity, but the relations remain uncertain.ObjectiveTo prospectively investigate the association of breastfeeding with the growth hormone- (GH) insulin-like growth factor- (IGF) axis, insulin sensitivity, body composition and body fat distribution in younger adulthood (18–37 years).DesignData from 233 (54% female) participants of a German cohort, the Dortmund Nutritional and Anthropometric Longitudinally Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, data were missing for some of the food variables because participants did not respond when asked about the consumption of that particular food item. There was also overlap between the confidence intervals of the OLS and quantile regression models and this may largely be due to the relatively modest sample size we used for this analyses approach (n = 466) compared to other studies [ 36 , 62 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data were missing for some of the food variables because participants did not respond when asked about the consumption of that particular food item. There was also overlap between the confidence intervals of the OLS and quantile regression models and this may largely be due to the relatively modest sample size we used for this analyses approach (n = 466) compared to other studies [ 36 , 62 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only other study that we are aware of that has examined being breast fed and circulating IGF-I concentrations in adults (n = 233) also found no significant association [30].…”
Section: Discussionmentioning
confidence: 75%
“…In some studies, breastfeeding has been found to lower the risk of the development of obesity during childhood [17,20] (for a review, see [21]). Recent analysis has indicated that breastfeeding has long-term favourable effects on adult body composition, extremes of adiposity and insulin metabolism; however, these effects were only observed in women [22]. By contrast, high protein intake from formula in infants seems to be associated with a higher body mass index, which lasts until the child is 6 years of age [23].…”
Section: Infancy and Early Childhoodmentioning
confidence: 99%